The Developing leadership character based on Pancasila in village government - Sriharjo, Sadono; Budimansyah, Dasim; Ruyadi, Yadi; Nurdin, Encep Syarief (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
-